10070: MET-02 NON-SMALL-CELL LUNG CANCER WITH SYNCHRONOUS BRAIN METASTASIS IN THE ERA OF MOLECULAR TARGETED DRUGS: TREATMENT OUTCOME AND RISK FACTORS. (16th December 2019) - Uzuka, Takeo; Higuchi, Fumi; Kim, Phyo; Ueki, Keisuke
Abstract: Brain metastasis is associated with worse prognosis in patients with non-small cell lung cancer (NSCLC). However, recent advances in molecular targeted therapy are rapidly changing the treatment strategy for NSCLC. Here, we conducted a retrospective study to clarify the prognosis and risk factors in NSCLC patients with synchronous brain metastasis. Seventy-four patients who were treated at our institute between Jan 2013 and Apr 2019 were included. The association between overall survival (OS) and clinicopathological features, such as neurological symptoms at diagnosis, histology, EGFR and ALK mutation status, number of intracranial metastases, extracranial systemic metastasis, Karnofsky performance status (KPS) at diagnosis, and initial therapy, were examined. OS was calculated from the day of diagnosis with brain metastasis or NSCLC. Of the 51 men and 23 women enrolled (median 70.0 years of age, range 40–84), 26 patients (35.1%) exhibited neurological symptoms at diagnosis. EGFR and ALK mutations were present in 24 (32.4%) patients. The median OS for all patients was 23.0 months. Factors significantly associated with worse OS in univariate analysis were symptomatic lesions and the absence of a driver mutation. Driver mutation status was only an independent prognosis factor in multivariate analysis. On lung-mol GPA score, the patients greater than or equal to 2.5 were significantly better prognosis compared with less than 2.5 (median OS: 40.0 VS 10.0 months, respectively). Our cohort of 74 NSCLC patients with synchronous brain metastasis had a median OS of 23.0 months. This much longer OS may reflect recent advances in treatment, particularly the availability of molecular targeted drugs. Lung-mol GPA score was considered as a useful tool to estimate the prognosis; thus, the information of KPS score, extracranial metastasis, brain metastases numbers, and driver mutation status are essential to build a treatment strategy for synchronous brain metastasis from NSCLC.